2002
DOI: 10.1182/blood.v100.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron overload and hepatitis C virus positivity in determining progression of liver fibrosis in thalassemia following bone marrow transplantation

Abstract: To identify the role of iron overload in the natural history of liver fibrosis, we reviewed serial hepatic biopsy specimens taken annually from patients cured of thalassemia major by bone marrow transplantation. The patients underwent transplantation between 1983 and 1989 and did not receive any chelation or antiviral therapy. Two hundred eleven patients (mean age, 8.7 ؎ 4 years) were evaluated for a median follow-up of 64 months (interquartile range, 43-98 months) by a median number of 5 (interquartile range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(191 citation statements)
references
References 24 publications
4
186
0
1
Order By: Relevance
“…Median serum ferritin levels in both patient groups at month 24 were lower than the threshold of 2500 ng/mL, which is associated with increased morbidity and mortality [22,23]. In parallel, mean LIC was reduced to below the threshold of 15 mg Fe/g dw by month 24, indicating a substantial reduction in iron burden (from baseline values above 30 mg Fe/g dw; considerably higher than in other monotherapy and combination therapy studies [9,10]) and a reduced risk of progressive organ damage and early death [24,25]. Despite substantial total body iron overload at baseline, the majority of patients enrolled in this study had a relatively low level of transfusional iron intake [<0.3 mg/(kg day) in 56% of patients] during the study, although iron intake varied from 0.1 to 0.7 mg/(kg day).…”
Section: Discussionmentioning
confidence: 97%
“…Median serum ferritin levels in both patient groups at month 24 were lower than the threshold of 2500 ng/mL, which is associated with increased morbidity and mortality [22,23]. In parallel, mean LIC was reduced to below the threshold of 15 mg Fe/g dw by month 24, indicating a substantial reduction in iron burden (from baseline values above 30 mg Fe/g dw; considerably higher than in other monotherapy and combination therapy studies [9,10]) and a reduced risk of progressive organ damage and early death [24,25]. Despite substantial total body iron overload at baseline, the majority of patients enrolled in this study had a relatively low level of transfusional iron intake [<0.3 mg/(kg day) in 56% of patients] during the study, although iron intake varied from 0.1 to 0.7 mg/(kg day).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, liver fibrosis was best predicted by quantitative liver iron. Angelucci et al [10] observed that both quantitative liver iron and HCV were strongly predictive of fibrosis. While we did not observe HCV as a predictor of fibrosis, it was the strongest predictor of inflammation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Iron overload is not usually taken into account when the indication for HSCT is a malignancy. Nevertheless, secondary iron overload may be frequent in this setting as these patients have often been heavily transfused prior to HSCT.…”
mentioning
confidence: 99%